Case of Late-Onset Fluid-Filled Descemet Membrane Detachment After Cataract Surgery and Its Management Using the Nd: YAG Laser. Issue 6 (June 2016) - Rathi, Harshal; Venugopal, Anitha; Rengappa, Ramakrishnan
Abstract : Purpose: To report a case of late-onset fluid-filled Descemet membrane detachment (DMD) after cataract surgery. Method: A case report with review of literature. Summary: The patient presented with DMD with turbid fluid accumulation, 19 months after cataract surgery. The DMD was successfully treated by draining the fluid into the anterior chamber via openings made in Descemet membrane using Nd:YAG laser (Neodymium-doped Yttrium Aluminum Garnet). To our knowledge, this is the first case report of fluid-filled DMD treated with the help of Nd:YAG laser.